Regenerating mahogany (Swietenia macrophylla King) on clearing in Mexico's Maya forest: the effects of clearing method and cleaning on seedling survival and growth - Snook, Laura K.; Negreros-Castillo, P. (2004)
To mimic catastropic disturbances which have favored the establishment of natural stands rich in mahogany (Swietenia macrophylla), two 5000 square meter clearings were established in each locations using each of three treatments: complete felling; slash and burn; machine-clearing with uprooted all prior vegetation. One to three months later, and after additional 12 months, twenty 4-month-old mahogany seedlings were planted in the center of each clearing, and nearby, under the forest canopy. Vines and competing vegetation were cleaned from arond the seedlings. Fifty-eight months late, only 5% of mahogany seedlings survived under the canopy, as compared to 32% on felled clearings, and 50% on burned or machine-made clearings. At 58 months uncleaned tress averaged 352 cm in height on burned clearings, 324 cm on machine-made clearings and 195 cm on felled clearings. Surviving seedlings planted under the forest canopy had grown less than 30 cm during the same period. On burned and machine-made clearings the effect of cleaning on growth was not statistically significant, but on felled clearings cleaning increased growth by 120%, to rates similar to those on burned clearings. Attack by the Hypsipyla grandella shootborer was significantly affected by cleaning. After 58 months, only 12% of seedlings on uncleaned plots had been attacked, compared to 44% of seedlings on cleaned plots. Cleaning also significantly increased vines, particularly on seedlings planted the year after clearings were created: 36% of all seedlings on cleaned plots had vines, as compared to 19% of uncleaned seedlings. In summary, planting mahogany seedlings under the forest canopy cannot be expected to regenerate mahogany trees. Mahogany seedlings survive and grow well on clearings, with no subsequent interventions, if planted shortly after these are opened by machine or burning. This approach to regeneration could be expected to yield densities of 100 commercial sized mahogany trees/ha among a matric of 400 naturally regenerated trees/ha of other species. At this rate, regenerating mahogany on clearings equivalent to 3% of the annual cutting area intervened at each harvest, could provide for replacement of mahogany trees harvested from the permanent forest reserves in the region.